Patterned polarizing film
A patterned polarizing film with a laminated cured liquid crystal film addresses manufacturing complexity and thickness issues, providing a thin, antireflection-enhanced circularly polarizing plate for display devices.
Patent Information
- Application Number
- JP2024172593
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2014-04-18
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing patterned polarizing films, such as those using polyvinyl alcohol and coated films, face challenges with complex manufacturing methods and thickness issues, lacking a patterned polarizing film made of a coated film.
A patterned polarizing film is developed by laminating a base material with a patterned cured liquid crystal film containing a polymerizable liquid crystal compound and dichroic dyes, achieving a thickness of 0.5-10 μm, with regions (A) having a degree of polarization of 10% or less and single transmittance of 80% or more, and regions (B) with 90% or more polarization and 40% transmittance, in striped or other shapes.
The solution results in a thin patterned circularly polarizing plate with excellent antireflection properties, allowing selective light control in display devices.
Smart Images

Figure 2024177300000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a patterned polarizing film. [Background technology]
[0002] Cited Document 1 describes a patterned polarizing film using a polyvinyl alcohol polarizing film and a circular polarizing plate including such a polarizing film. However, the polarizing film has problems in that the manufacturing method is complicated and the film thickness is large. Patent Document 2 describes a polarizing film including a polarizer made of a coating film and a circular polarizing plate including such a polarizing film. However, a patterned polarizing film containing a polarizer made of a coating film has not been known. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] U.S. Patent No. 5,327,285 [Patent Document 2] JP 2006-337892 A Summary of the Invention [Problem to be solved by the invention]
[0004] There has been a demand for a patterned polarizing film for obtaining a patterned circular polarizing plate that is thin and has excellent anti-reflection properties. [Means for solving the problem]
[0005] The present invention includes the following inventions. [1] A patterned polarizing film having a substrate and a patterned liquid crystal cured film laminated thereon, the liquid crystal cured film containing a polymer of a polymerizable liquid crystal compound and a plurality of dichroic dyes, and having a thickness of 0.5 to 10 μm; A region (A) having a polarization degree of 10% or less and a single transmittance of 80% or more; A patterned polarizing film having a polarization degree of 90% or more and a region (B) having a single transmittance of 40% or more. [2] The patterned polarizing film according to [1], wherein region (B) has the liquid crystal cured film. [3] The area of the continuous area (A) is 500 mm 2 The patterned polarizing film according to [1] or [2] below. [4] The area of the continuous area (B) is 500 mm 2 The patterned polarizing film according to [1] or [2] below. [5] The patterned polarizing film according to any one of [1] to [4], which has regions (A) and regions (B) in a striped pattern. [6] The patterned polarizing film according to [5], wherein the width of region (B) is 1 μm to 10 mm. [7] The patterned polarizing film according to [5], wherein the width of region (B) is 1 μm to 1 mm. [8] A patterned circular polarizing plate, wherein the substrate in the patterned polarizing film according to any one of [1] to [7] is a retardation film having a function as a quarter-wave plate. [9] A patterned circular polarizing plate comprising the patterned polarizing film according to any one of [1] to [7] and a retardation film having a quarter-wave plate function.
[10] The patterned circular polarizing plate according to [8] or [9], wherein the retardation film having a quarter-wave plate function has inverse wavelength dispersion characteristics.
[11] The patterned polarizing film according to any one of [1] to
[10] , wherein the substrate is a retardation film having a function as a quarter wave plate.
[12] The patterned polarizing film according to any one of [1] to
[10] , further comprising a retardation film having a function as a quarter wave plate.
[13] A patterned polarizing film according to
[11] or
[12] , wherein the retardation film having a quarter-wave plate function has inverse wavelength dispersion characteristics.
[14] The patterned polarizing film according to
[12] , wherein the substrate is a retardation film having a half-wave plate function.
[15] The patterned polarizing film according to any one of
[11] to
[14] , further comprising a positive C film. Effect of the Invention
[0006] According to the patterned polarizing film of the present invention, a thin patterned circular polarizing plate having excellent antireflection properties can be obtained. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic diagram of a cross section of a patterned polarizing film of the present invention. [Diagram 2] FIG. 2 is a schematic diagram of a patterned circular polarizing plate of the present invention having striped pattern regions. [Diagram 3] FIG. 2 is a schematic diagram of a patterned circular polarizing plate of the present invention having a circular pattern region. [Figure 4] FIG. 2 is a schematic diagram of a patterned circular polarizer. [Diagram 5] FIG. 1 is a schematic diagram showing the main parts of a continuous production method (roll to roll format) for the patterned polarizing film of the present invention. [Figure 6] FIG. 2 is a schematic diagram showing the main parts of a continuous manufacturing method for a patterned circular polarizing plate.
[0008] The patterned polarizing film of the present invention (hereinafter sometimes referred to as the present patterned polarizing film) is a laminate of a substrate and a patterned liquid crystal cured film. Here, the patterned liquid crystal cured film means that the liquid crystal cured film forms a desired pattern. The laminate is one in which the liquid crystal cured film forms a desired pattern on the substrate. It is preferable that an alignment film is further laminated between the substrate and the liquid crystal cured film. That is, the present patterned polarizing film is preferably a laminate of a substrate, an alignment film, and the liquid crystal cured film.
[0009] In this specification, the degree of polarization refers to the degree to which natural light is converted into linearly polarized light, and can take a value of 0 to 100% as defined by formula (11). If this value is 100%, it is completely linearly polarized light, and the closer this value is to 100%, the more selectively the light emitted from the polarizing film will be polarized, making it a superior polarizing film. Degree of polarization (%) = {(T 1 -T 2 ) / (T 1 +T 2 )}×100 (11) (Here, T 1 and T 2 are the transmittance when linearly polarized light is incident on the polarizing film, and T 1 is the transmittance measured when linearly polarized light parallel to the transmission axis is incident, T 2 is the transmittance measured when linearly polarized light parallel to the absorption axis direction is incident.)
[0010] In this specification, the single-piece transmittance is a value indicating the degree to which incident light is transmitted, and can take a value of 0 to 100% defined by the following formula (10). If this value is 100%, all of the incident light is transmitted, and if it is 0%, all of the incident light is absorbed or reflected. Single unit transmittance (%) = (T 1 +T 2 ) / 2 (10) (T 1 and T 2 has the same meaning as above.)
[0011] In this specification, for patterned polarizing films, which are so-called color polarizing films that contain dyes to control only light of a specific wavelength, the measured values at the maximum wavelength showing light absorption are defined as the polarization degree and the single transmittance. For patterned polarizing films, which are so-called neutral gray polarizing films obtained by mixing multiple dyes, the luminosity-corrected polarization degree and luminosity-corrected single transmittance are defined as the polarization degree and single transmittance in order to express the polarization performance in the entire visible light range.
[0012] The degree of polarization of the region obtained by masking with a photomask (hereinafter, sometimes referred to as region (A)) is preferably 5% or less, more preferably 1% or less. The degree of polarization tends to decrease as the amount of the liquid crystal cured film present in the region decreases. In other words, region (A) preferably does not have the liquid crystal cured film.
[0013] The closer the single transmittance of the region (A) is to 100%, the higher the transparency and the more practical it is for application to displays, etc. However, since this value includes the interfacial reflection loss associated with the refractive index difference between the air interface and the polarizing film, the theoretical maximum value is approximately 88 to 94%, depending on the material of the substrate, etc. The single transmittance of the region (A) is preferably 85% or more, and more preferably 88% or more. The single transmittance of this patterned polarizing film tends to improve as the amount of the liquid crystal cured film present in the region decreases.
[0014] The polarization degree of the region where the liquid crystal cured film is formed (hereinafter, sometimes referred to as region (B)) is preferably 92% or more, more preferably 95% or more. Region (B) usually has the liquid crystal cured film. The polarization degree of region (B) tends to increase as the degree of orientation order of the polymer of the polymerizable liquid crystal compound contained in the liquid crystal cured film increases.
[0015] The single transmittance of region (B) is approximately 44 to 47% as a theoretical maximum value because most of the polarized light in the direction perpendicular to the transmission axis direction is lost due to absorption. The single transmittance of region (B) is preferably 42% or more, and more preferably 44% or more.
[0016] The shape of the region (A) may be linear, stripe, circular, letter-like, or picture-like, and may be any shape, but is preferably linear. The shape of the region (B) may be linear, stripe, circular, letter-like, or picture-like, and may be any shape, but is preferably linear. It is preferable that the region (A) and the region (B) are in a striped pattern. That is, the pattern in this patterned polarizing film means a regular pattern. In other words, a polarizing film that has only irregular defects and simple edges that are not imparted with polarization properties and does not have a regular pattern does not fall under this patterned polarizing film.
[0017] When the shape of region (A) is linear, the width of the region is preferably 1 μm to 10 mm, more preferably 1 μm to 1 mm, and further preferably 1 μm to 100 μm.
[0018] When the shape of region (B) is linear, the width of the region is preferably 1 μm to 10 mm, more preferably 1 μm to 1 mm, and further preferably 1 μm to 100 μm.
[0019] When the regions (A) and (B) are arranged in a striped pattern, the width of the region (B) is preferably 1 μm to 10 mm, more preferably 1 μm to 1 mm, and further preferably 1 μm to 100 μm.
[0020] The area of the continuous region (A) is preferably 100 mm 2 More preferably, it is 50 mm or less. 2 The area of the continuous region (A) does not mean the total area of the region (A) in the entire patterned polarizing film, but means the area of each continuously formed region (A).
[0021] The area of the continuous region (B) is preferably 100 mm 2 More preferably, it is 50 mm or less. 2The area of the continuous region (B) does not mean the total area of the region (B) in the entire patterned polarizing film, but means the area of each continuously formed region (B).
[0022] The sum of the surface areas of the regions (A) and (B) with respect to the surface area of the present patterned polarizing film is preferably 90% or more, more preferably 95% or more, and even more preferably 99% or more.
[0023] 1 shows a schematic diagram of a cross section of the present patterned polarizing film 400. The present patterned polarizing film 400 is formed by laminating a substrate 420 and a patterned liquid crystal cured film 410. In the figure, H represents the thickness of the region where the liquid crystal cured film 410 is laminated, and h represents the thickness of the liquid crystal cured film.
[0024] In the present patterned polarizing film, the thickness of the region where the patterned liquid crystal cured film is laminated is usually 6 to 310 μm, and preferably 20 to 200 μm.
[0025] The thickness of the patterned liquid crystal cured film is usually 0.5 to 10 μm, and preferably 1 to 5 μm. The thickness of the liquid crystal cured film can be measured by an interference film thickness meter, a laser microscope, or a stylus film thickness meter.
[0026] In addition, the patterned liquid crystal cured film is preferably one that can obtain a Bragg peak in X-ray diffraction measurement. The liquid crystal cured film that can obtain such a Bragg peak exhibits, for example, a diffraction peak derived from a hexatic phase or a crystalline phase, and also tends to exhibit a high degree of polarization.
[0027] The patterned liquid crystal cured film is usually formed from a composition containing a polymerizable liquid crystal compound (hereinafter, sometimes referred to as a liquid crystal cured film-forming composition).
[0028] <Patterned circular polarizing plate> A patterned circular polarizing plate exhibiting circular polarization characteristics can be obtained by using a retardation film having a quarter-wave plate function as the substrate of the patterned polarizing film and laminating it at a specific angle. For example, this angle is preferably such that the slow axis (optical axis) of the retardation film having a quarter-wave plate function and the transmission axis of the region (B) are substantially 45°. A patterned circular polarizing plate can also be obtained by laminating the present patterned polarizing film with a retardation film having a ¼ wavelength plate function (hereinafter, sometimes referred to as a ¼ wavelength plate). In this case, it is preferable to laminate the present patterned polarizing film so that the transmission axis of the region (B) in the present patterned polarizing film and the slow axis (optical axis) of the ¼ wavelength plate are substantially at 45°. Substantially 45° is usually in the range of 45±5°. In addition, a patterned polarizing film that functions as an optical compensation film can be obtained by making the optical axes of the region (B) and the retardation film coincident with each other or perpendicular to each other.
[0029] The quarter-wave plate usually has the optical characteristic expressed by formula (40), and preferably has the optical characteristic expressed by formula (40-1). 100 <Re(550)<160 (40) 130 <Re(550)<150 (40-1) Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm.
[0030] Furthermore, the quarter-wave plate preferably has an inverse wavelength dispersion characteristic. The inverse wavelength dispersion characteristic means that the in-plane retardation value at a long wavelength is larger than the in-plane retardation value at a short wavelength, and preferably satisfies the optical characteristics expressed by formulas (50) and (51). Re(λ) represents the in-plane retardation value for light with a wavelength of λ nm. A patterned circular polarizer equipped with a quarter-wave plate having the optical characteristics expressed by formulas (50) and (51) tends to have excellent antireflection characteristics because it can obtain uniform polarization conversion characteristics for light of each wavelength in the visible light range. Re(450) / Re(550)≦1.00 (50) 1.00≦Re(630) / Re(550) (51)
[0031] The quarter-wave plate may be a coating film formed by polymerizing a polymerizable liquid crystal compound, or may be a stretched film. The quarter-wave plate having the optical properties represented by formula (50) and formula (51) can be obtained by polymerizing a specific polymerizable liquid crystal compound, or by stretching a film made of a polymer having a specific structure. The polymerizable liquid crystal compound may be the same as or different from the polymerizable liquid crystal compound contained in the liquid crystal cured film forming composition. A commercially available polymerizable liquid crystal compound may be used, and an example of a commercially available product is the product name "LC242" manufactured by BASF. In addition, a specific polymerizable liquid crystal compound satisfying formulas (50) and (51) is a compound described in Japanese Patent No. 5463666.
[0032] The direction of the slow axis of the quarter-wave plate is preferably 0°±10° or 90°±10° with respect to the longitudinal direction of the quarter-wave plate. By using such a quarter-wave plate, a patterned circular polarizing plate having the present patterned polarizing film can be easily obtained.
[0033] The direction of the slow axis of the coating film formed by polymerizing the polymerizable liquid crystal compound is determined by the alignment direction of the polymerizable liquid crystal compound. The direction of the slow axis of the stretched film varies depending on the stretching method, and the slow axis and optical axis are determined according to the stretching method, such as uniaxial, biaxial, or oblique stretching, etc. A stretched film uniaxially stretched in the longitudinal direction is preferred because it has high productivity and is versatile.
[0034] The patterned polarizing film and the quarter-wave plate are preferably laminated together by bonding with an adhesive.
[0035] The patterned polarizing film may be used after removing the substrate or the substrate and the alignment film. For example, the surface of the patterned polarizing film on which the patterned liquid crystal cured film is formed may be attached to another member such as a quarter-wave plate using an adhesive, and then the substrate or the substrate and the alignment film of the patterned polarizing film may be removed. In this case, the adhesive may be applied to the patterned polarizing film or to the other member. Preferably, the adhesive is applied to the patterned liquid crystal cured film of the patterned polarizing film or to the other member.
[0036] The patterned circular polarizing plate may further have one or more selected from the group consisting of a retardation film having a 1 / 2 wavelength plate function (hereinafter sometimes referred to as a 1 / 2 wavelength plate) and a positive C film, and may further have one or more selected from the group consisting of an anti-reflection layer, a brightness enhancement film, and a protective layer.
[0037] The protective layer plays a role of protecting the patterned liquid crystal cured film from external stimuli. The components forming the protective layer may be any components that do not damage the liquid crystal cured film when formed, and preferably include water-soluble polymers such as (meth)acrylic resins, epoxy resins, urethane resins, urea resins, silicone resins, and polyvinyl alcohol. Each of them may be dissolved in a solvent in the form of a polymer and applied onto the liquid crystal cured film, or may be dissolved in a solvent in the form of a monomer, or the monomer itself may be directly applied and then polymerized.
[0038] A half-wave plate usually has the optical characteristic expressed by equation (60). 200 <Re(550)<320 (60) Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm.
[0039] A positive C film typically has the optical properties expressed by equation (70). nx≒ny <nz (70) nx represents the principal refractive index in a direction parallel to the film plane in the refractive index ellipsoid formed by the positive C film. ny represents the principal refractive index in a direction parallel to the film plane and perpendicular to the direction of nx in the refractive index ellipsoid formed by the positive C film. nz represents the principal refractive index in a direction perpendicular to the film plane in the refractive index ellipsoid formed by the positive C film. The half-wave plate and the positive C film may be a coating film formed by polymerizing a polymerizable liquid crystal compound, or may be a stretched film.
[0040] Examples of the ¼ wavelength plate, ½ wavelength plate, and positive C film, which are coating films formed by polymerizing a polymerizable liquid crystal compound, include the retardation films described in JP-A-2010-31223, JP-A-2010-270108, JP-A-2011-6360, and JP-A-2011-207765.
[0041] An example of the quarter-wave plate that is a stretched film is "PureAce (registered trademark) WR" (manufactured by Teijin Limited). Examples of the positive C film, which is a stretched film, include the stretched film described in JP-A-2008-129465 and known multilayer extruded films.
[0042] The above-mentioned patterned circular polarizing plate has excellent anti-reflection properties. In the present invention, the patterned circular polarizing plate has excellent anti-reflection properties, which means that the desired region can be provided with anti-reflection properties. When light is incident on the reflector through the patterned circular polarizing plate and the reflectance is measured, the reflector has a region with high reflectance and a region with low reflectance. The region where region (A) is laminated corresponds to the region with high reflectance, and the region where region (B) is laminated corresponds to the region with low reflectance. By using a patterned circular polarizer having such characteristics, it is possible to impart anti-reflection properties only to the necessary areas of a display device.
[0043] The antireflection properties can be evaluated by measuring the reflectance, and also by measuring the ellipticity at each wavelength. The ellipticity is the ratio of the minor axis / major axis of circularly polarized light, and specifically, the ellipticity is 100% for completely circularly polarized light, and 0% for linearly polarized light. The closer the ellipticity at each wavelength is to 100%, the better the circular polarizing plate is, and the better the antireflection properties are. In other words, the closer the ellipticity of the region where the region (A) is laminated is to 0%, and the closer the ellipticity of the region having the region (B) is to 100%, the better the patterned circular polarizing plate is.
[0044] The reflectance of the region having the region (A) in the patterned circular polarizing plate is preferably 75% or more, more preferably 80% or more, and even more preferably 85% or more, based on the reflectance measured by irradiating light to the reflector without passing through the patterned circular polarizing plate being 100%. Similarly, the reflectance of the region where the region (B) is laminated is preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less.
[0045] In the patterned circular polarizing plate, the region having the region (A) has an ellipticity of preferably 20% or less, more preferably 5% or less, for light having a wavelength of 450 nm. Similarly, the ellipticity of preferably 20% or less, more preferably 5% or less, for light having a wavelength of 550 nm. Similarly, the ellipticity of preferably 20% or less, more preferably 5% or less, for light having a wavelength of 590 nm. Similarly, the ellipticity of preferably 20% or less, more preferably 5% or less, for light having a wavelength of 630 nm.
[0046] In the patterned circular polarizing plate, the ellipticity of the region where the region (B) is laminated is preferably 80% or more, more preferably 90% or more. In particular, in a neutral gray patterned polarizing film, the ellipticity for light with a wavelength of 450 nm is preferably 60% or more, more preferably 70% or more. Similarly, the ellipticity for light with a wavelength of 550 nm is preferably 80% or more, more preferably 90% or more. Similarly, the ellipticity for light with a wavelength of 590 nm is preferably 80% or more, more preferably 90% or more. Similarly, the ellipticity for light with a wavelength of 630 nm is preferably 60% or more, more preferably 70% or more.
[0047] FIG. 4 shows the structure of this patterned circular polarizer 10. 4(a) and (b) show a patterned circular polarizer 10 having a patterned liquid crystal cured film 1, a substrate 2, and a quarter-wave plate 6. FIG. 4(c) and (d) show a patterned circular polarizer 10 having a patterned liquid crystal cured film 1, a substrate 2, a ¼ wavelength plate 6 and a ½ wavelength plate 3. FIG. 4(e) shows a patterned circular polarizing plate 10 having a patterned liquid crystal cured film 1, a ¼ wavelength plate 6, and a ½ wavelength plate 3. Such a patterned circular polarizing plate can be obtained by using a ½ wavelength plate 3 as a substrate and forming a patterned liquid crystal cured film on its surface. Alternatively, the patterned liquid crystal cured film of this patterned polarizing film can be attached to the ½ wavelength plate 3, and then the substrate of this patterned polarizing film is removed, and then the ¼ wavelength plate 6 is laminated thereon. 4(f) to (h) show a patterned circular polarizer 10 having a patterned liquid crystal cured film 1, a ¼ wavelength plate 6, a ½ wavelength plate 3, and a positive C film 4. These patterned circular polarizers can be manufactured in the same manner as the patterned circular polarizer shown in FIG. 4(e).
[0048] When a ¼ wavelength plate and a ½ wavelength plate are laminated to form a patterned circular polarizing plate, it is preferable to first laminate the ½ wavelength plate so that the slow axis of the ½ wavelength plate is at 75° with respect to the absorption axis of the patterned liquid crystal cured film of the patterned polarizing film, and then laminate the ¼ wavelength plate so that the slow axis of the ¼ wavelength plate is at 15°. There is no restriction on the order of lamination of the positive C film, but the patterned liquid crystal cured film, the 1 / 2 wavelength plate, and the 1 / 4 wavelength plate of the patterned polarizing film must be laminated in this order. By laminating them in this way, the obtained patterned circular polarizing plate tends to have excellent anti-reflection properties because it has uniform polarization conversion properties for light of each wavelength in the visible light range.
[0049] The patterned polarizing film and the patterned circular polarizing plate can be cut as necessary and used in various display devices. The patterned polarizing film and the patterned circular polarizing plate are usually attached to a display device via an adhesive or a pressure-sensitive adhesive.
[0050] A display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. Examples of display devices having the present patterned polarizing film or the above patterned circular polarizing plate include liquid crystal display devices, organic electroluminescence (EL) display devices, inorganic electroluminescence (EL) display devices, electron emission display devices (e.g., field emission display devices (FEDs) and surface field emission displays (SEDs)), electronic paper (display devices using electronic ink or electrophoretic elements, plasma display devices, projection display devices (e.g., grating light valve (GLV) display devices, display devices having digital micromirror devices (DMDs)), and piezoelectric ceramic displays. Liquid crystal display devices include any of transmissive liquid crystal display devices, semi-transmissive liquid crystal display devices, reflective liquid crystal display devices, direct-view liquid crystal display devices, and projection liquid crystal display devices. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. The present patterned polarizing film and the above patterned circular polarizing plate are particularly effectively used in display devices such as organic electroluminescence (EL) display devices and inorganic electroluminescence (EL) display devices, as well as display devices including touch panels.
[0051] <Base material> The substrate may be a glass substrate or a resin substrate, but is preferably a resin substrate. By using a film substrate made of a resin, a thin patterned polarizing film can be obtained. The resin substrate is preferably a transparent resin substrate. The transparent resin substrate means a substrate having a light-transmitting property capable of transmitting light, particularly visible light, and the light-transmitting property means a property that the luminosity-corrected transmittance for light rays having a wavelength of 380 nm to 780 nm is 80% or more.
[0052] The substrate is preferably a quarter-wave plate. By using a quarter-wave plate as the substrate, a patterned circular polarizing plate can be obtained without laminating the present patterned polarizing film and the quarter-wave plate.
[0053] Preferred quarter-wave plates used as the substrate include the same as the quarter-wave plates described above.
[0054] The substrate may also be a half wave plate.
[0055] Examples of resins constituting the substrate include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers; cyclic olefin-based resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyethersulfone; polyether ketone; polyphenylene sulfide; and polyphenylene oxide. Preferred are cellulose esters, cyclic olefin-based resins, polycarbonate, polyethersulfone, polyethylene terephthalate, and polymethacrylic acid esters.
[0056] Cellulose ester is a material in which at least a part of the hydroxyl groups contained in cellulose is esterified, and can be obtained from the market. In addition, substrates containing cellulose esters can also be obtained from the market. Examples of commercially available substrates containing cellulose esters include FUJITAC (registered trademark) film (manufactured by FUJIFILM Corporation), KC8UX2M (manufactured by KONICA MINOLTA ADVANCED LAYER CO., LTD.), KC8UY (manufactured by KONICA MINOLTA ADVANCED LAYER CO., LTD.), and KC4UY (manufactured by KONICA MINOLTA ADVANCED LAYER CO., LTD.).
[0057] The cyclic olefin resin includes a polymer of a cyclic olefin such as norbornene or a polycyclic norbornene monomer, or a copolymer thereof. The cyclic olefin resin may include a ring-open structure, or may be a hydrogenated cyclic olefin resin including a ring-open structure. The cyclic olefin resin may include a structural unit derived from a chain olefin and a vinylated aromatic compound, within a range that does not significantly impair transparency or significantly increase moisture absorption. The cyclic olefin resin may also have a polar group introduced into its molecule. Examples of the linear olefin include ethylene and propylene, and examples of the vinylated aromatic compounds include styrene, α-methylstyrene, and alkyl-substituted styrenes.
[0058] When the cyclic olefin resin is a copolymer of a cyclic olefin and a chain olefin or a vinylated aromatic compound, the content of structural units derived from the cyclic olefin is usually 50 mol % or less, and preferably 15 to 50 mol %, based on the total structural units of the copolymer. When the cyclic olefin resin is a terpolymer of a cyclic olefin, a chain olefin, and a vinylated aromatic compound, the content of the structural unit derived from the chain olefin is usually 5-80 mol% based on the total structural units of the copolymer, and the content of the structural unit derived from the vinylated aromatic compound is usually 5-80 mol% based on the total structural units of the copolymer. Such a terpolymer has the advantage that the amount of expensive cyclic olefin used can be relatively reduced.
[0059] Cyclic olefin resins are commercially available. Examples of commercially available cyclic olefin resins include Topas (registered trademark) (manufactured by Ticona (Germany)), Arton (registered trademark) (manufactured by JSR Corporation), ZEONOR (registered trademark) (manufactured by Zeon Corporation), ZEONEX (registered trademark) (manufactured by Zeon Corporation), and APEL (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be formed into a film by known means such as a solvent casting method or a melt extrusion method to form a substrate. Examples of substrates containing commercially available cyclic olefin resins include S-Cina (registered trademark) (manufactured by Sekisui Chemical Co., Ltd.), SCA40 (registered trademark) (manufactured by Sekisui Chemical Co., Ltd.), ZEONOR FILM (registered trademark) (manufactured by Optes Co., Ltd.), and Arton (registered trademark) film (manufactured by JSR Corporation).
[0060] The substrate may be subjected to a surface treatment. Examples of the surface treatment method include a method of treating the substrate surface with corona or plasma under an atmosphere of vacuum to atmospheric pressure, a method of laser treating the substrate surface, a method of ozone treating the substrate surface, a method of saponifying the substrate surface, a method of flame treating the substrate surface, a method of applying a coupling agent to the substrate surface, a method of primer treating the substrate surface, and a graft polymerization method in which reactive monomers or reactive polymers are attached to the substrate surface and then reacted by irradiating radiation, plasma or ultraviolet light. Among these, a method of treating the substrate surface with corona or plasma under an atmosphere of vacuum to atmospheric pressure is preferred.
[0061] Methods for performing surface treatment of a substrate with corona or plasma include a method for placing the substrate between opposing electrodes under pressure close to atmospheric pressure and generating corona or plasma to perform surface treatment of the substrate, a method for flowing a gas between opposing electrodes, converting the gas into plasma between the electrodes, and spraying the plasmatized gas onto the substrate, and a method for generating glow discharge plasma under low pressure conditions to perform surface treatment of the substrate.
[0062] Among these, a method of placing a substrate between opposing electrodes under a pressure close to atmospheric pressure, generating a corona or plasma to perform surface treatment of the substrate, or a method of flowing a gas between opposing electrodes, converting the gas into plasma between the electrodes, and spraying the plasma gas onto the substrate is preferred. Such surface treatment using corona or plasma is usually performed using a commercially available surface treatment device.
[0063] The substrate may have a protective film on the surface opposite to the surface on which the liquid crystal cured film-forming composition is applied. Examples of the protective film include films of polyethylene, polyethylene terephthalate, polycarbonate, polyolefin, and the like, as well as films further having an adhesive layer. Among them, polyethylene terephthalate is preferred because it is less thermally deformed during drying. By having a protective film on the surface opposite to the surface on which the liquid crystal cured film-forming composition is applied, it is possible to suppress the shaking of the film during transport of the substrate and slight vibration of the coating surface, thereby improving the uniformity of the coating film.
[0064] The thickness of the substrate is preferably thin in terms of the weight that allows practical handling, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the substrate is usually 5 to 300 μm, and preferably 20 to 200 μm.
[0065] The length of the substrate in the longitudinal direction is usually 10 to 3000 m, preferably 100 to 2000 m, and the length of the substrate in the lateral direction is usually 0.1 to 5 m, preferably 0.2 to 2 m.
[0066] <Alignment film> The alignment film in the present invention has an alignment regulating force for aligning the polymerizable liquid crystal compound in a desired direction. The alignment film is preferably one that has solvent resistance such that the liquid crystal cured film-forming composition is not dissolved by application, and also has heat resistance in a heat treatment for removing the solvent and for orienting the polymerizable liquid crystal compound. Examples of such an alignment film include an alignment film containing an alignment polymer, a photoalignment film, and a groove alignment film in which a concave-convex pattern or a plurality of grooves are formed on the surface to achieve alignment.
[0067] Examples of the oriented polymer include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. Two or more oriented polymers may be used in combination.
[0068] An alignment film containing an alignment polymer is usually formed on the surface of a substrate by applying a composition in which an alignment polymer is dissolved in a solvent (hereinafter, sometimes referred to as an alignment polymer composition) to the substrate and then removing the solvent, or by applying an alignment polymer composition to the substrate, removing the solvent, and rubbing the substrate (rubbing method).
[0069] Examples of the solvent include water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, and other alcohol solvents, ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, ethyl lactate, and other ester solvents, acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, methyl isobutyl ketone, and other ketone solvents, pentane, hexane, heptane, and other aliphatic hydrocarbon solvents, toluene, xylene, and other aromatic hydrocarbon solvents, acetonitrile, and other nitrile solvents, tetrahydrofuran, dimethoxyethane, and other ether solvents, and chloroform, chlorobenzene, and other chlorinated hydrocarbon solvents. These solvents may be used alone or in combination of two or more.
[0070] The concentration of the orienting polymer in the orienting polymer composition may be within a range in which the orienting polymer can be completely dissolved in the solvent, and is preferably 0.1 to 20 mass % in terms of solid content relative to the solution, and more preferably about 0.1 to 10 mass %.
[0071] As the oriented polymer composition, a commercially available alignment film material may be used as it is. Examples of commercially available alignment film materials include Sunever (registered trademark) (manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark) (manufactured by JSR Corporation).
[0072] Examples of a method for applying the oriented polymer composition to a substrate include known methods such as spin coating, extrusion, gravure coating, die coating, slit coating, bar coating, and applicator coating, and printing methods such as flexography. When the present patterned polarizing film is produced by a roll-to-roll continuous production method described below, the coating method usually employs a printing method such as gravure coating, die coating, or flexography.
[0073] Methods for removing the solvent contained in the orientable polymer composition include natural drying, ventilation drying, heat drying, and reduced pressure drying.
[0074] In order to impart an alignment control force to the alignment film, rubbing is performed as necessary (rubbing method). By selecting the rubbing direction, the direction of the alignment control force can be arbitrarily controlled.
[0075] An example of a method for imparting an orientation control force by a rubbing method is to bring an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to the substrate and annealing the composition into contact with a rotating rubbing roll wrapped with a rubbing cloth.
[0076] A photo-alignment film is usually formed on the surface of a substrate by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter, sometimes referred to as a "photo-alignment film-forming composition") to the substrate and irradiating the substrate with light (preferably polarized UV). Photo-alignment films are more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated light.
[0077] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that are the origin of liquid crystal alignment ability, such as molecular alignment induction caused by light irradiation or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond) is particularly preferred.
[0078] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0079] Among them, photoreactive groups involved in photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small and a photoalignment film having excellent thermal stability and stability over time is easily obtained. As the polymer having a photoreactive group, one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred.
[0080] The solvent contained in the composition for forming a photo-alignment film may be the same as the solvent contained in the above-mentioned alignable polymer composition, and may be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.
[0081] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted depending on the type of polymer or monomer and the thickness of the intended photo-alignment film, but is preferably at least 0.2% by mass, and more preferably in the range of 0.3 to 10% by mass. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range that does not significantly impair the properties of the photo-alignment film.
[0082] The method for applying the composition for forming a photo-alignment film to a substrate may be the same as the method for applying the alignable polymer composition to a substrate. The method for removing the solvent from the applied composition for forming a photo-alignment film may be the same as the method for removing the solvent from the alignable polymer composition.
[0083] The polarized light may be irradiated by directly irradiating the polarized UV light onto the composition for forming a photo-aligned film coated on the substrate after removing the solvent, or by irradiating the polarized light from the substrate side and transmitting the polarized light. In addition, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. These lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The polarized UV light can be irradiated by passing the light from the light source through an appropriate polarizer. As such a polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0084] If masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.
[0085] A groove alignment film is a film that can align liquid crystals by using a concave-convex pattern or multiple grooves on the film surface. HV Kennell et al. reported that when liquid crystal molecules are placed on a substrate with multiple equally spaced linear grooves, the liquid crystal molecules are oriented along the grooves (Physical Review A24(5), p. 2713, 1981).
[0086] Specific methods for forming a groove alignment film on the surface of a substrate include a method in which a photosensitive polyimide surface is exposed to light through an exposure mask having slits in a periodic pattern, followed by development and rinsing to remove unnecessary polyimide film to form a concave-convex pattern; a method in which a UV-cured resin layer is formed on a plate-shaped master having grooves on its surface, and the resin layer is transferred to a substrate film and then cured; a method in which a substrate film on which a UV-cured resin layer has been formed is transported, and a roll-shaped master having a plurality of grooves is pressed against the surface of the UV-cured resin layer to form concave-convex patterns and then cured; and the like. Methods described in JP-A-6-34976 and JP-A-2011-242743 can be used.
[0087] Among the above methods, a method in which a roll-shaped master having a plurality of grooves is pressed against the surface of a UV-cured resin layer to form projections and recesses and then cured is preferred. Stainless steel (SUS) can be used as the roll-shaped master from the viewpoint of durability.
[0088] As the UV curable resin, a polymer of a monofunctional acrylate, a polymer of a polyfunctional acrylate, or a polymer of a mixture thereof can be used. A monofunctional acrylate is a compound having one group (hereinafter sometimes referred to as a (meth)acryloyloxy group) selected from the group consisting of an acryloyloxy group (CH2=CH-COO-) and a methacryloyloxy group (CH2=C(CH3)-COO-) in the molecule.
[0089] Examples of monofunctional acrylates having one (meth)acryloyloxy group include alkyl (meth)acrylates having 4 to 16 carbon atoms, β-carboxyalkyl (meth)acrylates having 2 to 14 carbon atoms, alkylated phenyl (meth)acrylates having 2 to 14 carbon atoms, methoxypolyethylene glycol (meth)acrylates, phenoxypolyethylene glycol (meth)acrylates, and isobornyl (meth)acrylates.
[0090] The polyfunctional acrylate is usually a compound having 2 to 6 (meth)acryloyloxy groups in the molecule.
[0091] Examples of bifunctional acrylates having two (meth)acryloyloxy groups include 1,3-butanediol di(meth)acrylate; 1,6-hexanediol di(meth)acrylate; ethylene glycol di(meth)acrylate; diethylene glycol di(meth)acrylate; neopentyl glycol di(meth)acrylate; triethylene glycol di(meth)acrylate; tetraethylene glycol di(meth)acrylate; polyethylene glycol diacrylate; bis(acryloyloxyethyl)ether of bisphenol A; ethoxylated bisphenol A di(meth)acrylate; propoxylated neopentyl glycol di(meth)acrylate; ethoxylated neopentyl glycol di(meth)acrylate, and 3-methylpentanediol di(meth)acrylate.
[0092] Examples of polyfunctional acrylates having 3 to 6 (meth)acryloyloxy groups include: Trimethylolpropane tri(meth)acrylate;Pentaerythritol tri(meth)acrylate;Tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate;Ethoxylated trimethylolpropane tri(meth)acrylate;Propoxylated trimethylolpropane tri(meth)acrylate;Pentaerythritol tetra(meth)acrylate;Dipentaerythritol penta(meth)acrylate;Dipentaerythritol hexa(meth)acrylate;Tripentaerythritol tetra(meth)acrylate;Tripentaerythritol penta(meth)acrylate;Tripentaerythritol hexa(meth)acrylate;Tripentaerythritol hepta(meth)acrylate;Tripentaerythritol octa(meth)acrylate; Reaction products of pentaerythritol tri(meth)acrylate with acid anhydride;Reaction products of dipentaerythritol penta(meth)acrylate with acid anhydride; Reaction products of tripentaerythritol hepta(meth)acrylate with acid anhydride; Caprolactone modified trimethylolpropane tri(meth)acrylate;Caprolactone modified pentaerythritol tri(meth)acrylate;Caprolactone modified tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate;Caprolactone modified pentaerythritol tetra(meth)acrylate;Caprolactone modified dipentaerythritol penta(meth)acrylate;Caprolactone modified dipentaerythritol hexa(meth)acrylate;Caprolactone modified tripentaerythritol tetra(meth)acrylate;Caprolactone modified tripentaerythritol Examples of the polyfunctional acrylate include tripentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hepta(meth)acrylate, caprolactone-modified tripentaerythritol octa(meth)acrylate, a reaction product of caprolactone-modified pentaerythritol tri(meth)acrylate and an acid anhydride, a reaction product of caprolactone-modified dipentaerythritol penta(meth)acrylate and an acid anhydride, and a reaction product of caprolactone-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride. In the specific examples of the polyfunctional acrylate shown here, (meth)acrylate means acrylate or methacrylate. In addition, caprolactone-modified means that a ring-opened product or a ring-opened polymer of caprolactone is introduced between the alcohol-derived site and the (meth)acryloyloxy group of the (meth)acrylate compound.
[0093] Such polyfunctional acrylates may also be commercially available products. Such commercially available products include A-DOD-N, A-HD-N, A-NOD-N, APG-100, APG-200, APG-400, A-GLY-9E, A-GLY-20E, A-TMM-3, A-TMPT, AD-TMP, ATM-35E, A-TMMT, A-9550, A-DPH, HD-N, NOD-N, NPG, TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd.), "ARONIX M-220", "M-325", "M-240", "M-270", "M-309", "M-310", "M-321", "M-350", "M-360", "M-305", "M-306", and "M-450". , "M-451", "M-408", "M-400", "M-402", "M-403", "M-404", "M-405", "M-406" (manufactured by Toa Gosei Co., Ltd.), "EBECRYL11", "145", "150", "40", "140", "180", DPGDA, HDDA, TPGDA, HPNDA, PETIA, PETRA, TMPTA, TMPEOTA, DPHA, EBECRYL series (manufactured by Daicel-Cytec Co., Ltd.), and the like.
[0094] As for the unevenness of the groove alignment film, the width of the protrusions is preferably 0.05 to 5 μm, the width of the recesses is preferably 0.1 to 5 μm, and the depth of the unevenness is preferably 2 μm or less, more preferably 0.01 to 1 μm. Within these ranges, liquid crystal alignment with little alignment disorder can be obtained.
[0095] The thickness of the alignment film is usually 10 nm to 10,000 nm, preferably 10 nm to 1,000 nm, and more preferably 10 nm to 500 nm.
[0096] <Polymerizable liquid crystal compound> The polymerizable liquid crystal compound is a compound that has a polymerizable group and has liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator described later. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property may be a thermotropic liquid crystal or a lyotropic liquid crystal, and the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal.
[0097] As the polymerizable liquid crystal compound, a smectic liquid crystal compound is preferred in that higher polarization characteristics can be obtained, and a higher-order smectic liquid crystal compound is more preferred. Among them, a higher-order smectic liquid crystal compound that forms a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase, or a smectic L phase is more preferred, and a higher-order smectic liquid crystal compound that forms a smectic B phase, a smectic F phase, or a smectic I phase is more preferred. When the liquid crystal phase formed by the polymerizable liquid crystal compound is one of these higher-order smectic phases, a liquid crystal cured film with a higher degree of orientation order can be produced, and a high degree of polarization can be obtained. In addition, such a liquid crystal cured film with a high degree of orientation order is one that can obtain a Bragg peak derived from a higher-order structure such as a hexatic phase or a crystal phase in X-ray diffraction measurement. The Bragg peak is a peak derived from the periodic structure of molecular orientation, and a film having a periodic interval of 3.0 to 6.0 Å can be obtained. Specific examples of such compounds include a compound represented by the following formula (1) (hereinafter, sometimes referred to as compound (1)). The polymerizable liquid crystal compound may be used alone or in combination.
[0098] U 1 -V 1-W 1 -X 1 -Y 1 -X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (1) [In formula (1), X 1 , X 2 and X 3 each independently represents a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent, provided that X 1 , X 2 and X 3 At least one of the groups is a 1,4-phenylene group which may have a substituent. -CH2- constituting the cyclohexane-1,4-diyl group may be replaced by -O-, -S- or -NR-. R represents an alkyl group having 1 to 6 carbon atoms or a phenyl group. Y 1 and Y 2 are each independently -CH2CH2-, -CH2O-, -COO-, -OCOO-, a single bond, -N=N-, -CR a =CR b -, -C≡C- or -CR a =N-. R a and R b each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. U 1 and U 2 represents a hydrogen atom or a polymerizable group, and at least one of them is a polymerizable group. W 1 and W 2 represent each independently a single bond, -O-, -S-, -COO- or -OCOO-. V 1 and V 2 each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and -CH2- constituting the alkanediyl group may be replaced by -O-, -S- or -NH-.]
[0099] In compound (1), X 1 , X 2 and X 3 At least one of these is preferably a 1,4-phenylene group which may have a substituent. The 1,4-phenylene group which may have a substituent is preferably unsubstituted. The cyclohexane-1,4-diyl group which may have a substituent is preferably a trans-cyclohexane-1,4-diyl group which may have a substituent, and the trans-cyclohexane-1,4-diyl group which may have a substituent is preferably unsubstituted.
[0100] Examples of the substituent that the 1,4-phenylene group which may have a substituent or the cyclohexane-1,4-diyl group which may have a substituent include an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, and a butyl group, a cyano group, and a halogen atom.
[0101] Y 1 is preferably -CH2CH2-, -COO- or a single bond, and Y 2 is preferably -CH2CH2- or -CH2O-.
[0102] U 2 is a hydrogen atom or a polymerizable group. 1 is a hydrogen atom or a polymerizable group, and is preferably a polymerizable group. 1 and U 2 Preferably, both of and are polymerizable groups, and more preferably, both are photopolymerizable groups. A polymerizable liquid crystal compound having a photopolymerizable group is advantageous in that it can be polymerized under lower temperature conditions.
[0103] U 1 and U 2The polymerizable groups represented by may be different from each other, but are preferably the same. Examples of the polymerizable group include vinyl group, vinyloxy group, 1-chlorovinyl group, isopropenyl group, 4-vinylphenyl group, acryloyloxy group, methacryloyloxy group, oxiranyl group, and oxetanyl group. Among them, acryloyloxy group, methacryloyloxy group, vinyloxy group, oxiranyl group, and oxetanyl group are preferred, and acryloyloxy group is more preferred.
[0104] V 1 and V 2 Examples of the alkanediyl group represented by the formula (I) include a methylene group, an ethylene group, a propane-1,3-diyl group, a butane-1,3-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, a heptane-1,7-diyl group, an octane-1,8-diyl group, a decane-1,10-diyl group, a tetradecane-1,14-diyl group, and an icosane-1,20-diyl group. 1 and V 2 is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms. Examples of the substituent that the optionally substituted alkanediyl group having 1 to 20 carbon atoms may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted, linear alkanediyl group.
[0105] W 1 and W 2 are each independently preferably a single bond or -O-.
[0106] Specific examples of compound (1) include compounds represented by formulas (1-1) to (1-23). When compound (1) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.
[0107] TIFF2024177300000002.tif155140
[0108] TIFF2024177300000003.tif91136
[0109] TIFF2024177300000004.tif89145
[0110] TIFF2024177300000005.tif84145
[0111] Among the exemplified compounds (1), at least one selected from the group consisting of the compounds represented by formula (1-2), formula (1-3), formula (1-4), formula (1-6), formula (1-7), formula (1-8), formula (1-13), formula (1-14) and formula (1-15) is preferable.
[0112] The exemplified compound (1) can be used alone or in combination in the composition for forming a liquid crystal cured film. In addition, when two or more kinds of polymerizable liquid crystal compounds are combined, it is preferable that at least one of them is compound (1), and it is more preferable that two or more kinds are compound (1). By combining them, liquid crystallinity may be temporarily maintained even at a temperature below the liquid crystal-crystal phase transition temperature. The mixing ratio when combining two kinds of polymerizable liquid crystal compounds is usually 1:99 to 50:50, preferably 5:95 to 50:50, and more preferably 10:90 to 50:50.
[0113] The polymerizable liquid crystal compound can be produced by a known method, for example, as described in Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996) and Japanese Patent No. 4719156.
[0114] The content ratio of the polymerizable liquid crystal compound in the liquid crystal cured film-forming composition is usually 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 80 to 94 parts by mass, and even more preferably 80 to 90 parts by mass, based on 100 parts by mass of the solid content of the liquid crystal cured film-forming composition, from the viewpoint of increasing the alignment property of the polymerizable liquid crystal compound. In this specification, the solid content refers to the total amount of components excluding the solvent from the liquid crystal cured film-forming composition.
[0115] The liquid crystal cured film-forming composition preferably contains a dichroic dye, a polymerization initiator, and a solvent. It may also contain a sensitizer, a polymerization inhibitor, a leveling agent, and a polymerizable non-liquid crystal compound. That is, the liquid crystal cured film preferably contains a dichroic dye.
[0116] <Dichroic dye> A dichroic dye is a dye that has different absorbance in the long axis direction of the molecule and absorbance in the short axis direction.
[0117] The dichroic dye preferably has a maximum absorption wavelength (λMAX) in the range of 300 to 700 nm. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes, among which azo dyes are preferred. Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes, and preferably bisazo dyes and trisazo dyes. The dichroic dyes may be used alone or in combination, but when polarization performance is required over the entire visible light range, it is preferable to combine three or more types. In this case, it is particularly preferable to combine three or more types of azo compounds.
[0118] An example of the azo dye is a compound represented by formula (2) (hereinafter sometimes referred to as "compound (2)"). A 1 (-N=NA 2 ) p -N=NA 3 (2) [In formula (2), A 1 and A 3 A each independently represents a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. 2 represents an optionally substituted 1,4-phenylene group, an optionally substituted naphthalene-1,4-diyl group, or an optionally substituted divalent heterocyclic group. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of A 2 may be the same or different independently of each other.
[0119] Examples of the monovalent heterocyclic group include groups in which one hydrogen atom has been removed from a heterocyclic compound such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole. Examples of the divalent heterocyclic group include groups in which two hydrogen atoms have been removed from the above heterocyclic compounds.
[0120] A 1 and A 3 Phenyl, naphthyl and monovalent heterocyclic groups in the above formula, and A 2 In the above, the p-phenylene group, the naphthalene-1,4-diyl group, and the divalent heterocyclic group may have any of the following substituents: an alkyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, and a butoxy group; a fluorinated alkyl group having 1 to 4 carbon atoms, such as a trifluoromethyl group; a cyano group; a nitro group; a halogen atom; and a substituted or unsubstituted amino group, such as an amino group, a diethylamino group, and a pyrrolidino group (the substituted amino group means an amino group having one or two alkyl groups having 1 to 6 carbon atoms, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. The unsubstituted amino group is -NH2). Specific examples of the alkyl group having 1 to 6 carbon atoms are the same as those exemplified as the optional substituents of the phenylene group of the compound (1).
[0121] Among the compounds (2), the compounds represented by the following formulas (2-1) to (2-6) are preferred.
[0122] TIFF2024177300000006.tif83109
[0123] TIFF2024177300000007.tif74127 [In formulas (2-1) to (2-6), B 1 ~B 20 each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the substituted amino group and the unsubstituted amino group are defined above), a chlorine atom, or a trifluoromethyl group. n1 to n4 each independently represent an integer of 0 to 3. If n1 is 2 or more, multiple B 2 may be the same or different independently of each other, If n2 is 2 or more, multiple B 6 may be the same or different independently of each other, If n3 is 2 or more, multiple B 9 may be the same or different independently of each other, If n4 is 2 or more, multiple B 14 may be the same or different independently of each other.
[0124] The anthraquinone dye is preferably a compound represented by formula (2-7). TIFF2024177300000008.tif3179 [In formula (2-7), R 1 ~R 8 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0125] The oxazine dye is preferably a compound represented by formula (2-8). TIFF2024177300000009.tif3177 [In formula (2-8), R 9 ~R 15 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0126] The acridine dye is preferably a compound represented by formula (2-9). TIFF2024177300000010.tif3171[In formula (2-9), R 16 ~R 23 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.]
[0127] R in formula (2-7), formula (2-8) and formula (2-9) x Examples of the alkyl group having 1 to 4 carbon atoms represented by the formula (I) include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group, and examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, a toluyl group, a xylyl group, and a naphthyl group.
[0128] As the cyanine dye, the compounds represented by formula (2-10) and formula (2-11) are preferred. TIFF2024177300000011.tif1555[In formula (2-10), D 1 and D. 2 each independently represents a group represented by any one of formulas (2-10a) to (2-10d). TIFF2024177300000012.tif27128 n5 represents an integer from 1 to 3.
[0129] TIFF2024177300000013.tif1856 [In formula (2-11), D 3 and D. 4 each independently represents a group represented by any one of formulas (2-11a) to (2-11h). TIFF2024177300000014.tif64110 n6 represents an integer from 1 to 3.
[0130] The content of the dichroic dye in the liquid crystal cured film-forming composition is preferably 0.1 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, even more preferably 0.1 to 10 parts by mass, and particularly preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the solid content of the liquid crystal cured film-forming composition, from the viewpoint of improving the alignment of the dichroic dye. If the content of the dichroic dye is within this range, it is preferable because the liquid crystal alignment of the polymerizable liquid crystal compound is not easily disturbed.
[0131] <Polymerization initiator> The polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferable.
[0132] Examples of the polymerization initiator include a benzoin compound, a benzophenone compound, an alkylphenone compound, an acylphosphine oxide compound, a triazine compound, an iodonium salt, and a sulfonium salt.
[0133] Examples of the benzoin compound include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0134] Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.
[0135] Examples of alkylphenone compounds include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethane-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexyl phenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one.
[0136] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0137] Examples of the triazine compound include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl]-1,3,5-triazine. 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine.
[0138] The polymerization initiator may be commercially available. Examples of commercially available polymerization initiators include Irgacure (registered trademark) 907, 184, 651, 819, 250, and 369 (manufactured by BASF Japan Co., Ltd.); Seikuol (registered trademark) BZ, Z, and BEE (manufactured by Seiko Chemical Co., Ltd.); Kayacure (registered trademark) BP100 (Nippon Kayaku Co., Ltd.) and UVI-6992 (manufactured by Dow Chemical Co., Ltd.); Adeka Optomer SP-152 and SP-170 (ADEKA Corporation); TAZ-A and TAZ-PP (manufactured by Nippon SiberHegner Co., Ltd.); and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).
[0139] The content of the polymerization initiator is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound, from the viewpoint of preventing the alignment of the polymerizable liquid crystal compound from being disturbed.
[0140] <Solvent> The solvent is preferably one which can completely dissolve the polymerizable liquid crystal compound, and is preferably a solvent which is inactive to the polymerization reaction of the polymerizable liquid crystal compound.
[0141] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorine-containing solvents such as chloroform and chlorobenzene. These solvents may be used alone or in combination.
[0142] The content of the solvent is preferably 50 to 98% by mass based on the total amount of the liquid crystal cured film-forming composition, in other words, the solid content in the liquid crystal cured film-forming composition is preferably 2 to 50% by mass. When the solid content is 50% by mass or less, the viscosity of the liquid crystal cured film-forming composition is low, and the thickness of the liquid crystal cured film becomes substantially uniform, so that the liquid crystal cured film tends to be less prone to unevenness. In addition, the solid content can be determined in consideration of the thickness of the liquid crystal cured film to be produced.
[0143] <Sensitizer> The sensitizer is preferably a photosensitizer. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.), anthracene compounds such as anthracene and alkoxy group-containing anthracene (e.g., dibutoxyanthracene, etc.), phenothiazine, rubrene, etc.
[0144] The content of the sensitizer in the liquid crystal cured film-forming composition is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0145] <Polymerization inhibitor> Examples of the polymerization inhibitor include radical scavengers such as hydroquinone, alkoxy group-containing hydroquinone, alkoxy group-containing catechol (e.g., butylcatechol, etc.), pyrogallol, and 2,2,6,6-tetramethyl-1-piperidinyloxy radical; thiophenols; β-naphthylamines, and β-naphthols.
[0146] The content of the polymerization inhibitor in the liquid crystal cured film-forming composition is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0147] <Leveling agent> The leveling agent has a function of adjusting the fluidity of the liquid crystal cured film-forming composition and making the coating film of the liquid crystal cured film-forming composition flatter, and can be exemplified by a surfactant. Preferred leveling agents include a leveling agent mainly composed of a polyacrylate compound and a leveling agent mainly composed of a fluorine atom-containing compound.
[0148] Examples of leveling agents containing a polyacrylate compound as a main component include BYK-350, BYK-352, BYK-353, BYK-354, BYK-355, BYK-358N, BYK-361N, BYK-380, BYK-381, and BYK-392 (manufactured by BYK Chemie).
[0149] Examples of leveling agents containing a fluorine atom-containing compound as a main component include Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-471, F-477, F-479, F-482, and F-483 (DIC Corporation); Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, and SA-100 (AGC Seimi Chemical Co., Ltd.); E1830 and E5844 (Daikin Fine Chemical Research Institute Co., Ltd.); and F-top (registered trademark) EF301, EF303, EF351, and EF352 (Mitsubishi Materials Electronic Chemicals Co., Ltd.).
[0150] The content of the leveling agent in the liquid crystal cured film-forming composition is usually 0.3 parts by mass or more and 5 parts by mass or less, and preferably 0.5 parts by mass or more and 3 parts by mass or less, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, it is easy to align the polymerizable liquid crystal compound horizontally, and the obtained liquid crystal cured film tends to be smoother, which is preferable. When the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, it is not preferable because the obtained liquid crystal cured film tends to be uneven. The liquid crystal cured film forming composition may contain two or more types of leveling agents.
[0151] <Polymerizable non-liquid crystal compound> The liquid crystal cured film-forming composition may contain a polymerizable non-liquid crystal compound. By containing the polymerizable non-liquid crystal compound, the crosslink density of the polymerization reactive site can be increased, and the strength of the liquid crystal cured film can be improved.
[0152] The polymerizable non-liquid crystal compound preferably has at least one polymerizable group selected from the group consisting of an acryloyl group, a methacryloyl group, and an isocyanate group, more preferably has 2 to 10 polymerizable groups, and further preferably has 3 to 8 polymerizable groups.
[0153] The content of the polymerizable non-liquid crystal compound in the liquid crystal cured film-forming composition is usually 0.1 to 30 parts by mass, and preferably 0.5 to 10 parts by mass, based on 100 parts by mass of the solid content of the liquid crystal cured film-forming composition.
[0154] A liquid crystal cured film is obtained by polymerizing the polymerizable liquid crystal compound. The liquid crystal cured film containing the polymerizable liquid crystal compound polymerized while maintaining the smectic liquid crystal phase has higher polarization performance such as polarization degree than a conventional host-guest type polarizing film, i.e., a polarizing film obtained by polymerizing a polymerizable liquid crystal compound while maintaining the nematic liquid crystal phase, and is also superior in polarization performance such as polarization degree and strength compared to a film coated with only a dichroic dye or a lyotropic liquid crystal.
[0155] <Manufacturing method of this patterned polarizing film> The present patterned polarizing film is usually produced by a production method including the following steps (1) to (4). (1) A step of applying a composition containing a polymerizable liquid crystal compound and a dichroic dye (hereinafter, sometimes referred to as a liquid crystal cured film-forming composition) to the surface of a substrate or a substrate on which an alignment film has been formed. (2) A step of orienting the applied polymerizable liquid crystal compound and dichroic dye (3) A step of irradiating the aligned polymerizable liquid crystal compound with active energy rays through a photomask to obtain a liquid crystal cured film containing a polymerized product of the polymerizable liquid crystal compound and a non-polymerized polymerizable liquid crystal compound. (4) A process of washing the liquid crystal cured film with a solvent in which the saturated solubility of the dichroic dye at 23° C. is 1% by mass or less, and removing the unpolymerized polymerizable liquid crystal compound to obtain a patterned liquid crystal cured film.
[0156] <Step (1)> The method of applying the composition containing the polymerizable liquid crystal compound (the composition for forming the liquid crystal cured film) can be the same as the method of applying the alignment polymer composition to the substrate. In this process, the surface of the substrate on which the alignment film is formed means the surface of the alignment film formed on the substrate.
[0157] <Step (2)> When the liquid crystal cured film-forming composition contains a solvent, the solvent is usually removed from the applied liquid crystal cured film-forming composition. Examples of the method for removing the solvent include natural drying, ventilation drying, heat drying, and reduced pressure drying.
[0158] The coated polymerizable liquid crystal compound is usually heated to a temperature at which it transitions to a solution state or higher, and then cooled to a temperature at which the liquid crystal is aligned, thereby forming a liquid crystal phase.
[0159] The temperature at which the applied polymerizable liquid crystal compound is oriented may be determined in advance by observing the texture of a composition containing the polymerizable liquid crystal compound. The removal of the solvent and the alignment of the liquid crystal may be performed simultaneously. The temperature at this time is preferably in the range of 50 to 200°C, depending on the type of the solvent to be removed and the type of the polymerizable liquid crystal compound, and more preferably in the range of 80 to 130°C when the substrate is a resin substrate.
[0160] When a patterned polarizing film that functions as a circular polarizing plate is obtained using a substrate that is a quarter-wave plate, the orientation direction of the polymerizable liquid crystal compound is preferably such that the transmission axis of the obtained cured liquid crystal film and the slow axis (optical axis) of the substrate are substantially at 45°. Substantially 45° is usually in the range of 45±5°. In addition, a patterned polarizing film that functions as an optical compensation film can be obtained by making the optical axes of the cured liquid crystal film and the substrate coincident with each other or perpendicular to each other.
[0161] <Step (3)> The aligned polymerizable liquid crystal compound is polymerized by irradiating it with active energy rays through a photomask, during which the polymerizable liquid crystal compound in the area masked by the photomask does not polymerize. The irradiation of active energy rays is preferably performed in a state where a photomask is pressed against the aligned polymerizable liquid crystal compound. By performing the irradiation in a pressed state, a liquid crystal cured film having a pattern with clearly defined edges can be obtained.
[0162] The polymerized polymerizable liquid crystal compound becomes a liquid crystal cured film. The liquid crystal cured film containing the polymerized polymerizable liquid crystal compound while maintaining the smectic liquid crystal phase has higher polarization performance such as polarization degree than a conventional host-guest type polarizing film, i.e., a polarizing film obtained by polymerizing a polymerizable liquid crystal compound while maintaining the nematic liquid crystal phase, and is also superior in polarization performance such as polarization degree and strength compared to a film coated with only a dichroic dye or a lyotropic liquid crystal.
[0163] The shape of the unmasked area of the photomask can be any shape, and various designs are possible by processing the photomask into a line, a strip, a circle, a character, or a figure. Also, the shape of the masked area of the photomask can be any shape.
[0164] The light source of the active energy ray is preferably a parallel light so as to have the shape and width of the pattern of the set photomask. The light source of the active energy ray may be any light source that generates ultraviolet rays, electron beams, X-rays, etc. Preferred is a light source having an emission distribution of 400 nm or less in wavelength, such as a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a chemical lamp, a black light lamp, a microwave excited mercury lamp, a metal halide lamp, etc. It is more preferable that the active energy rays are ultraviolet rays parallel to the normal direction of the substrate.
[0165] The irradiation energy of the active energy rays is 10 to 5000 mJ / cm in the wavelength region effective for activating the polymerization initiator. 2 It is preferable to set the value so as to be within a range of 100 to 2000 mJ / cm. 2 The irradiation exposure is 10 mJ / cm 2 If the temperature is too low, the polymerizable liquid crystal compound will not be cured sufficiently, and the cured liquid crystal film will tend to dissolve in the washing step.
[0166] <Step (4)> The unpolymerized polymerizable liquid crystal compound in the area masked by the photomask is removed by washing the liquid crystal cured film containing the polymerized polymerizable liquid crystal compound and the unpolymerized polymerizable liquid crystal compound. The cleaning is usually performed with a solvent. Examples of the method of cleaning with a solvent include a method of immersing the substrate on which the liquid crystal cured film is formed in a solvent to dissolve the unpolymerized polymerizable liquid crystal compound in the solvent, and a method of spraying the solvent onto the substrate on which the liquid crystal cured film is formed to dissolve the unpolymerized polymerizable liquid crystal compound in the solvent.
[0167] The solvent used for washing is preferably a solvent that dissolves the polymerizable liquid crystal compound but does not dissolve the liquid crystal cured film.Specific examples of the solvent include water; alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ether solvents such as diethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane, and mixed solvents thereof.Preferably, the solvent contains an alcohol solvent, and more preferably, the solvent is an alcohol solvent.
[0168] If washed with a solvent, it may be dried. Thus, a patterned polarizing film having a patterned liquid crystal cured film is obtained.
[0169] The patterned polarizing film obtained by this production method can impart high polarizing properties by printing only to necessary areas of a display device or the like.
[0170] FIG. 2 is a schematic diagram of the present patterned polarizing film 100 having striped patterned regions. The portion 110 shown in gray fill represents the area where the liquid crystal cured film was formed, the portion 120 shown in white represents the area obtained by masking with a photomask, and the portion 130 shown in dots represents the area where the liquid crystal cured film-forming composition was not applied (simply an edge portion). FIG. 3 is a schematic diagram of the present patterned polarizing film 101 having circular patterned regions. The numerals 110, 120 and 130 have the same meaning as the patterned polarizing film 100 described above.
[0171] <Continuous manufacturing method for this patterned polarizing film> The present patterned polarizing film is preferably produced continuously in a roll-to-roll system. An example of the main part of a method for continuously producing the film in a roll-to-roll system will be described with reference to Fig. 5 .
[0172] The first roll 210 in which the substrate is wound around the first winding core 210A is, for example, easily available on the market. Examples of substrates available on the market in the form of such a roll include films made of cellulose ester, cyclic olefin resin, polycarbonate, polyethylene terephthalate, or polymethacrylic acid ester, among the substrates already exemplified.
[0173] Next, the substrate is unwound from the first roll 210. The method of unwinding the substrate is performed by providing a suitable rotating means on the winding core 210A of the first roll 210 and rotating the first roll 210 by the rotating means. Alternatively, a suitable auxiliary roll 300 may be provided in the direction in which the substrate is transported from the first roll 210, and the substrate may be unwound by the rotating means of the auxiliary roll 300. Furthermore, by providing a rotating means on both the first winding core 210A and the auxiliary roll 300, the substrate may be unwound while applying an appropriate tension to the substrate.
[0174] When the substrate unwound from the first roll 210 passes through the coating device 211A, the composition for forming a photo-alignment film is coated on the surface of the substrate by the coating device 211A. As the coating device 211A for continuously coating the composition for forming a photo-alignment film in this manner, gravure coating, die coating and flexography are preferable.
[0175] The substrate that has passed through the coating device 211A is transported to the drying oven 212A, where it is dried, and a first coating film is continuously formed on the substrate surface. For example, a hot air drying oven that combines a ventilation drying method and a heat drying method is used as the drying oven 212A. The set temperature of the drying oven 212A is determined according to the type of solvent contained in the composition for forming a photo-alignment film. The drying oven 212A may be composed of multiple zones with different set temperatures, or may be a drying oven in which multiple drying ovens with different set temperatures are installed in series.
[0176] The obtained first coating film is irradiated with polarized light by polarized UV irradiation device 213A, thereby obtaining a photo-alignment film.
[0177] Next, the substrate on which the photo-alignment film is formed passes through the coating device 211B. After the coating device 211B applies a composition containing a polymerizable liquid crystal compound and a solvent onto the photo-alignment film, the coating passes through the drying oven 212B to obtain a second coating film in which the polymerizable liquid crystal compound is aligned. The drying oven 212B has a role of removing the solvent from the composition containing the polymerizable liquid crystal compound and a solvent applied onto the photo-alignment film, and also a role of providing thermal energy so that the polymerizable liquid crystal compound contained in the composition is aligned. The drying oven 212B may be composed of multiple zones with different set temperatures, as with the drying oven 212A, or may be a drying oven in which multiple drying ovens with different set temperatures are installed in series.
[0178] The second coating film is transported to the active energy ray irradiation device 213B in a state where the polymerizable liquid crystal compound contained in the second coating film is aligned. In the active energy ray irradiation device 213B, a photomask (not shown) is placed on the second coating film, and the second coating film is further irradiated with active energy rays. By irradiating the second coating film with active energy rays by the active energy ray irradiation device 213B, the polymerizable liquid crystal compound in the unmasked area is polymerized in an aligned state, and a liquid crystal cured film containing a polymerized product of the polymerizable liquid crystal compound and an unpolymerized polymerizable liquid crystal compound is obtained.
[0179] The substrate on which the liquid crystal cured film is formed is passed through a solvent tank 214 filled with a solvent. The polymerizable liquid crystal compound in the area that was masked during the irradiation of the active energy rays is washed away to form an area (A).
[0180] The substrate is then passed through a drying furnace 212C to remove the solvent adhering to the surface.
[0181] The patterned polarizing film thus continuously produced is wound around the second winding core 220A to obtain the form of the second roll 220. When winding, co-winding using an appropriate spacer may be performed.
[0182] In this manner, the substrate passes from the first roll 210 through the coating device 211A, the drying furnace 212A, the polarized UV irradiation device 213A, the coating device 211B, the drying furnace 212B, the active energy ray irradiation device 213B, the solvent bath 214, and the drying furnace 212C in that order, whereby the present patterned polarizing film can be continuously produced in a roll to roll format.
[0183] In addition, in the manufacturing method shown in FIG. 5, a method for continuously manufacturing from the substrate to the present patterned polarizing film is shown, but, for example, the substrate is passed from a first roll through coating device 211A, drying furnace 212A, and polarized UV irradiation device 213A in this order, and then wound up around a core to produce a roll-shaped laminate of substrate and photoalignment film, and further, the roll-shaped laminate is unwound and passed through coating device 211B, drying furnace 212B, active energy ray irradiation device 213B, solvent bath 214, and drying furnace 212C in this order, thereby continuously manufacturing the present patterned polarizing film.
[0184] When the present patterned polarizing film is produced in the form of the second roll 220, the long present patterned polarizing film may be unwound from the second roll 220, cut to a specified size, and then a quarter-wave plate may be laminated to the cut patterned polarizing film to produce a patterned circular polarizing plate; however, by preparing a third roll on which a long quarter-wave plate is wound around a core, a long patterned circular polarizing plate can also be produced continuously.
[0185] A method for continuously producing a long patterned circular polarizing plate will be described with reference to FIG. The manufacturing method includes: a step of continuously unwinding the patterned polarizing film from a second roll 220 and continuously unwinding a long length of the quarter-wave plate from a third roll 230 around which the long length of the quarter-wave plate is wound; a step of continuously laminating the patterned polarizing film and the long quarter-wave plate to obtain a long patterned circular polarizing plate; The obtained long patterned circularly polarizing plate is wound around a fourth winding core 240A to obtain a fourth roll 240. This method is so-called roll to roll lamination. An adhesive may be used for lamination. EXAMPLES
[0186] The present invention will be described in more detail below with reference to examples. In the examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.
[0187] Example 1 [Production of composition for forming photoalignment film] A composition for forming a photoalignment film was obtained by mixing the following components and stirring the resulting mixture at 80° C. for 1 hour. The following polymer having a photoreactive group was synthesized by the method described in JP-A-2013-33248. Polymers with photoreactive groups: TIFF2024177300000015.tif19150 Solvent: o-xylene 98 parts
[0188] [Production of liquid crystal cured film-forming composition 1] The following components were mixed and stirred at 80°C for 1 hour to obtain a liquid crystal cured film-forming composition. The azo-based dye described in the examples of JP-A-2013-101328 was used as the dichroic dye. The polymerizable liquid crystal compounds represented by formulae (1-6) and (1-7) were synthesized according to the method described in JP-A-4719156. Polymerizable liquid crystal compound: TIFF2024177300000016.tif1615075 copy TIFF2024177300000017.tif1613825 copy Dichroic dye 1: TIFF2024177300000018.tif10882.8 copies Polymerization initiator; 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure 369; manufactured by Chiba Specialty Chemicals) 6 parts Leveling agent; Polyacrylate compound (BYK-361N; manufactured by BYK-Chemie) 1.2 parts Solvent: o-xylene 250 parts
[0189] [Production of patterned polarizing film (1)] A triacetyl cellulose film (Konica Minolta Advanced Layer, Inc., KC4UY-TAC, thickness 40 μm) was cut into a size of 80 mm × 80 mm, and its surface was subjected to a corona treatment (AGF-B10, Kasuga Electric Co., Ltd.). A composition for forming a photoalignment film was applied to the corona-treated film surface using a bar coater, and then dried for 1 minute in a drying oven set at 120°C to obtain a first coating film. A polarized UV irradiation device (SPOT CURE (registered trademark) SP-7; Ushio Inc.) was used to irradiate the first coating film with polarized UV at 0° to the longitudinal direction of the film at 50 mJ / cm. 2 A photo-alignment film was formed by irradiating the liquid crystal cured film with an integrated light amount (based on 313 nm). A liquid crystal cured film-forming composition was applied to an area of 70 mm x 80 mm on the obtained photo-alignment film using a bar coater, and then dried for 1 minute in a drying oven set at 110°C to obtain a second coating film in which the polymerizable liquid crystal compound and the dichroic dye were aligned. The center of the second coating film was irradiated with ultraviolet light (under a nitrogen atmosphere, wavelength: 365 nm, integrated light amount at wavelength 365 nm: 1000 mJ / cm) using a high-pressure mercury lamp (UniCure (registered trademark) VB-15201BY-A, manufactured by Ushio Inc.) through a 40 mm x 40 mm photomask (line width 275 μm). 2 ) to obtain a liquid crystal cured film containing a polymerized product of the polymerizable liquid crystal compound and an unpolymerized polymerizable liquid crystal compound. The film having the obtained liquid crystal cured film was immersed in ethanol for 3 minutes to wash and remove the unpolymerized polymerizable liquid crystal compound, thereby obtaining a patterned polarizing film (1) having a striped pattern. The obtained patterned polarizing film (1) had the same shape as the schematic diagram of the patterned polarizing film of the present invention shown in FIG. 2.
[0190] [Evaluation of patterned polarizing film (1)] [Measurement of polarization degree and single transmittance] The polarization degree and single transmittance of the patterned polarizing film (1) were measured in the region where the patterned liquid crystal cured film was formed and in the region obtained by masking with a photomask as follows. 1 ) and transmittance along the absorption axis (T 2) was measured in the wavelength range of 380 to 680 nm in 2 nm steps by the double beam method using a spectrophotometer (Shimadzu UV-3150) equipped with a polarizer folder. The transmittance (T 1 ), and the transmittance along the absorption axis (T 2 ) and the degree of polarization and the single transmittance were calculated using the following formulas (10) and (11). As a result, in the region where the patterned liquid crystal cured film was formed, λMAX was 520 nm, the degree of polarization was 92.8%, and the single transmittance was 44.0%. In the region obtained by masking with a photomask, no light absorption was measured, the degree of polarization was 0%, and the single transmittance was 92%. Single unit transmittance (%) = (T 1 +T 2 ) / 2 (10) Degree of polarization (%) = {(T 1 -T 2 ) / (T 1 +T 2 )}×100 (11) [Film thickness measurement] The thickness of the patterned liquid crystal cured film in the patterned polarizing film (1) was measured using a laser microscope (LEXT, manufactured by Olympus Corporation) and was found to be 2.0 μm. The patterned polarizing film (1) had a thickness of 42 μm. [Line width measurement] The width of the striped liquid crystal cured film in the patterned polarizing film (1) was measured using a polarizing microscope. When the widths of five different points of the liquid crystal cured film were measured, the widths were 271 μm, 275 μm, 275 μm, 274 μm, and 278 μm, respectively. This was almost the same as the line width of the photomask (275 μm), and it was confirmed that patterning was possible with the line width of the photomask. In addition, the continuous area of the striped liquid crystal cured film was 8.3 mm 2 It was. [Ovality measurement] A quarter-wave plate (ZEONORFILM (registered trademark), manufactured by Zeon Corporation, in-plane retardation value Ro: 138 nm), which is a uniaxially stretched film of a cyclic olefin resin, was attached to the patterned polarizing film (1) via an adhesive to obtain a patterned circular polarizing plate (1). The ellipticity of the patterned liquid crystal cured film-formed region of the patterned circular polarizing plate (1) and the region obtained by masking with a photomask were measured for light with a wavelength of 550 nm using an automatic birefringence meter "KOBRA (registered trademark)" manufactured by Oji Scientific Instruments Co., Ltd. As a result, the ellipticity of the region where the patterned liquid crystal cured film was formed at a wavelength of 550 nm was 92%. The ellipticity of the region obtained by masking with a photomask at a wavelength of 550 nm was 0%. That is, a patterned circular polarizing plate having excellent antireflection properties for light of a specific wavelength was obtained from the patterned polarizing film (1).
[0191] Example 2 [Production of liquid crystal cured film forming composition 2] A patterned polarizing film (2) was produced in the same manner as in Example 1, except that a liquid crystal cured film-forming composition 2 was produced by further adding the following dichroic dye to the liquid crystal cured film-forming composition 1 of Example 1 and used as a coating liquid. Dichroic dye 2: TIFF2024177300000019.tif11892.8 copies Dichroic dye 3: TIFF2024177300000020.tif14942.8 copies [Evaluation of patterned polarizing film] [Measurement of polarization degree and single transmittance] The polarization degree and the single transmittance were measured in the same manner as in Example 1. Visibility correction was performed using a 2-degree visual field (C light source) according to JIS Z 8701 to calculate the visibility-corrected polarization degree (Py) and visibility-corrected single transmittance (Ty). As a result, Py=92.3% and Ty=43.7% in the region where the patterned liquid crystal cured film was formed. Py=0% and Ty=92.0% in the region obtained by masking with a photomask. [Film thickness measurement] The thickness of the patterned liquid crystal cured film in the patterned polarizing film (2) was measured using a laser microscope (LEXT (registered trademark), manufactured by Olympus Corporation) to be 2.0 μm, and the film loss rate of the liquid crystal cured film containing the polymerized product of the polymerizable liquid crystal compound before and after washing was 0%. The thickness of the patterned polarizing film (2) was 42 μm. [Line width measurement] The width of the striped liquid crystal cured film in the patterned polarizing film (2) was measured using a polarizing microscope. When the widths of five different points of the liquid crystal cured film were measured, the widths were 275 μm, 272 μm, 275 μm, 274 μm, and 274 μm, respectively. This was almost the same as the line width of the photomask (275 μm), and it was confirmed that patterning was possible with the line width of the photomask. In addition, the continuous area of the striped liquid crystal cured film was 8.3 mm 2 It was. [Ovality measurement] A ¼ wavelength plate (PureAce (registered trademark) WRF-S, manufactured by Teijin Limited), which is a uniaxially stretched film, was attached to the patterned polarizing film (2) via an adhesive to obtain a patterned circular polarizing plate (2). The retardation (Re(λ)) of the quarter-wave plate was measured using an automatic birefringence meter "KOBRA (registered trademark)" manufactured by Oji Scientific Instruments Co., Ltd., and the results were Re(450) = 132 nm, Re(550) = 145 nm, Re(590) = 147 nm, Re(630) = 148 nm, and Re(750) = 151 nm, showing reverse wavelength dispersion characteristics. The ellipticity for light with wavelengths of 450 nm, 550 nm, 590 nm, 630 nm, and 750 nm was measured using an automatic birefringence meter "KOBRA (registered trademark)" manufactured by Oji Scientific Instruments Co., Ltd. for the region in which the patterned liquid crystal cured film of the patterned circular polarizing plate (2) was formed and the region obtained by masking with a photomask. As a result, the ellipticity of the region where the patterned liquid crystal cured film was formed was 77% at a wavelength of 450 nm, 91% at 550 nm, 99% at 590 nm, and 92% at 630 nm. The ellipticity of the region obtained by masking with a photomask was 0% at a wavelength of 450 nm, 0% at 550 nm, 0% at 590 nm, and 0% at 630 nm. In other words, a patterned circular polarizing plate with excellent anti-reflection properties was obtained from the patterned polarizing film (2).
[0192] Example 3 A patterned polarizing film (3) was produced in the same manner as in Example 1, except that the uniaxially stretched film (PureAce (registered trademark) WRF-S, manufactured by Teijin Limited, thickness 50 μm) used in Example 2 was used instead of the triacetyl cellulose film, and further, the polarized UV light was irradiated so that the polarization vibration direction of the polarized UV light was at 45° with respect to the slow axis of the uniaxially stretched film. [Evaluation of Patterned Polarizing Film (6)] [Measurement of polarization degree and single transmittance] The luminosity-corrected polarization degree (Py) and luminosity-corrected single transmittance (Ty) were measured in the same manner as in Example 2. As a result, Py=95.7% and Ty=41.7% in the region where the patterned liquid crystal cured film was formed. Py=0% and Ty=89.0% in the region obtained by masking with a photomask. [Film thickness measurement] The thickness of the patterned liquid crystal cured film in the patterned polarizing film (3) was measured using a laser microscope (LEXT (registered trademark), manufactured by Olympus Corporation) and was found to be 2.5 μm. The thickness of the patterned polarizing film (3) was 53 μm. [Line width measurement] The width of the striped liquid crystal cured film in the patterned polarizing film (3) was measured using a polarizing microscope. When the widths of five different points of the liquid crystal cured film were measured, the widths were 276 μm, 277 μm, 276 μm, 274 μm, and 273 μm, respectively. This was almost the same as the line width of the photomask (275 μm), and it was confirmed that patterning was possible with the line width of the photomask. In addition, the continuous area of the striped liquid crystal cured film was 8.3 mm 2 It was. [Ovality measurement] The ellipticity of the patterned liquid crystal cured film of the patterned polarizing film (3) was measured for light with wavelengths of 450 nm, 550 nm, 590 nm, 630 nm, and 750 nm using an automatic birefringence meter "KOBRA (registered trademark)" manufactured by Oji Scientific Instruments Co., Ltd. As a result, the ellipticity of the patterned liquid crystal cured film of the region formed was 78% at wavelength 450 nm, 92% at wavelength 550 nm, 96% at wavelength 590 nm, and 88% at wavelength 630 nm. In the area masked with the photomask, the ellipticity was 0% at wavelengths of 450 nm, 550 nm, 590 nm, and 630 nm. In other words, the patterned polarizing film (3) is a patterned circular polarizing plate with excellent antireflection properties. [Industrial Applicability]
[0193] The patterned polarizing film of the present invention is useful for obtaining a patterned circular polarizing plate which is thin and has excellent antireflection properties.
[0194] 1. Patterned liquid crystal cured film 2 Base material 3 1 / 2 wave plate 4 Positive C film 6 1 / 4 wave plate 10-pattern circular polarizer 100 This patterned polarizing film has striped pattern areas. 101 This patterned polarizing film has a circular pattern area. 110 Area where liquid crystal hardened film is formed 120 Area obtained by masking with a photomask 130 Area where the liquid crystal cured film forming composition was not applied 210 Roll 1 210A core 220 Roll 2 220A core 211A, 211B Coating equipment 212A,212B,212C Drying oven 213A Polarized UV irradiation device 213B Active energy ray irradiation equipment 214 Solvent tank 300 Auxiliary Roll 230 Third Roll 230A core 240 4th Roll 240A core 300 Auxiliary Roll Cross section of 400-pattern polarizing film 410 Liquid crystal cured film 420 Base material H Thickness of the area where the liquid crystal cured film is laminated h Thickness of the liquid crystal cured film
Claims
1. A patterned polarizing film having a substrate and a patterned liquid crystal cured film laminated thereon, The liquid crystal cured film contains a polymer of a polymerizable liquid crystal compound and a plurality of dichroic dyes and has a thickness of 0.5 to 10 μm; A region (A) having a polarization degree of 10% or less and a single transmittance of 80% or more; A patterned polarizing film having a region (B) having a polarization degree of 90% or more and a single-unit transmittance of 40% or more.
2. The patterned polarizing film according to claim 1 , wherein the region (B) comprises the liquid crystal cured film.
3. 3. The patterned polarizing film according to claim 1, wherein the regions (A) and (B) each independently have at least one shape selected from the group consisting of a line, a band, a circle, a letter, and a graphic shape.
4. 4. The patterned polarizing film according to claim 1, wherein the regions (A) are linear and have a width of 1 μm to 10 mm.
5. 4. The patterned polarizing film according to claim 1, wherein the regions (B) are linear and have a width of 1 μm to 10 mm.
6. The area of the continuous region (A) is 500 mm 2 4. The patterned polarizing film according to claim 1, wherein:
7. The area of the continuous region (B) is 500 mm 2 4. The patterned polarizing film according to claim 1, wherein:
8. 8. The patterned polarizing film according to claim 1, which has the regions (A) and (B) in a striped pattern.
9. 9. The patterned polarizing film according to claim 8, wherein the width of region (B) is 1 μm to 10 mm.
10. 9. The patterned polarizing film according to claim 8, wherein the width of region (B) is 1 μm to 1 mm.
11. 11. The patterned polarizing film according to claim 1, wherein the substrate is a retardation film having a quarter wave plate function.
12. The patterned polarizing film according to any one of claims 1 to 10, further comprising a retardation film having a quarter wave plate function.
13. 13. The patterned polarizing film according to claim 11, wherein the retardation film having a quarter wave plate function has a reverse wavelength dispersion characteristic.
14. 13. The patterned polarizing film according to claim 12, wherein the substrate is a retardation film having a function as a half-wave plate.
15. The patterned circular polarizing plate according to any one of claims 11 to 10, further comprising a positive C film.
Citation Information
Patent Citations
Elliptically polarizing plate and image display using the same
JP2007328310A
Polarizing film, circularly polarizing plate and their manufacturing method
JP2013101328A
Elliptically polarizing plate, liquid crystal panel, liquid crystal display device, and image display device
JP2006337892A
Methods for manufacturing micropolarizers
US5327285A
